INVENTORY OF INVASIVE INSECT SPECIES IN COBAN TALUN, BATU CITY - Saputri, Priska Anggun; Putri, Jihan Fahira Adinda; Zahwa, Amirah Rusdanti; Prasetyaningsih, Dyah; Afifah, Nurul; Denatalia, Sherlita Crisne; Fardhani, Indra (Universitas Medan Area, 2024)
Insects are the greatest number of animal species on earth. Invasive species are insects that are non-native to a particular area, and negatively affect other organisms in their ecosystem. This study examines the diversity of invasive insect species with the aim of determining the diversity of invasive insect species found in Coban Talun, Batu City, effective and sustainable invasive insect control strategies, as well as conservation actions that need to be taken to maintain the balance of the ecosystem in Coban Talun. This study used a descriptive method using exploration techniques at three observation locations to collect data. This method used was observation of the focus of the problem under study, namely invasive insects which are the object of research. The data collection technique was carried out by exploring the location under study by observing, documenting, describing and identifying specimens using various literature. The results of the study obtained were the discovery of several types of invasive insects including black cockroaches (Phyllodromica maculata), large heath butterflies (Coenonympha tullia), green grasshoppers (Tettigonia viridissima), flies (Musca domestica), Mexican bean beetles (Epilachna varivestis), and soldier beetles (Rhagonycha recta). Invasive types of insects need population control by using natural insecticides so that the ecosystem in Coban Talun remains balanced.